Angular independent silicon detector for dosimetry in external beam radiotherapy. Issue 8 (17th July 2015) - Petasecca, M.; Alhujaili, S.; Aldosari, A. H.; Fuduli, I.; Newall, M.; Porumb, C. S.; Carolan, M.; Nitschke, K.; Lerch, M. L. F.; Kalliopuska, J.; Perevertaylo, V.; Rosenfeld, A. B.
Abstract : Purpose: In this work, the "edgeless" silicon detector technology is investigated, in combination with an innovative packaging solution, to manufacture silicon detectors with negligible angular response. The new diode is also characterized as a dosimeter for radiotherapy with the aim to verify its suitability as a single detector for in vivo dosimetry as well as large area 2D array that does not require angular correction to their response. Methods: For the characterisation of the "edgeless‐drop‐in" detector technology, a set of samples have been manufactured with different sensitive areas (1 × 1 and 0.5 × 0.5 mm 2 ) and different thicknesses (0.1 and 0.5 mm) in four different combinations of top and peripheral p–n junction fabricated on p‐type and n‐type silicon substrates. The diode probes were tested in terms of percentage depth dose (PDD), dose rate, and linearity and compared to ion chambers. Measurements of the output factor have been compared to film. The angular response of the diodes probes has been tested in a cylindrical PMMA phantom, rotated with bidirectional accuracy of 0.25° under 10 × 10 cm 2 6 MV Linac photon beam. The radiation hardness has been investigated as well as the effect of radiation damage on the angular and dose rate response of the diode probes when irradiated with photons from a Co‐60 gamma source up to dose of 40 kGy. Results: The PDDs measured by the edgeless detectors show an agreement with the data obtained using ion chambers within ±2%. The output factor measured with the smallest area edgeless diodes (0.5 × 0.5 mm 2 —0.1 and 0.5 mm thick) matches EBT3 film to within 2% for square field size from 10 to 0.5 cm side equivalent distance. The dose rate dependence in a dose per pulse range of 0.9 × 10 −5 –2.7 × 10 −4 Gy/pulse was less than −7% and +300% for diodes fabricated on p‐type and n‐type substrates, respectively. The edgeless diodes fabricated on the p‐type substrate demonstrated degradation of the response as a function of the irradiation dose within 5%–15%, while diodes on the n‐type substrate show a variation of approximately 30% after 40 kGy. The angular response of all probes is minimal (within 2%) but the N on N and P on P configurations show the best performances with an angular dependence of ±1.0% between 0° and 180° in the transversal direction. In this configuration, the space charge region of the passive diode extends from the behind and sidewall toward the anode on the top providing beneficial electric field distribution in the peripheral area of the diode. Such performance has also been tested after irradiation by Co‐60 up to 40 kGy with no measurable change in angular response. Conclusions: A new edgeless‐drop‐in silicon diode fabrication and packaging technology has been used to develop detectors that show no significant angular dependence in their response for dosimetry in radiation therapy. From the characterisation of the diodes, proposed in a wide range of different geometries and configurations, the authors recommend the P‐on‐P detectors in conjunction with "drop in" packaging technology as the candidate for further development as single diode probe or 2D diode array for dosimetry in radiotherapy.